Referral patterns in elderly emergency department visits - Alessandra Buja; Marco Fusco; Patrizia Furlan; Chiara Bertoncello; Tatjana Baldovin; Patrizia Casale; Adriano Marcolongo; Vincenzo Baldo (Istituto Superiore di Sanità, 2013)
OBJECTIVE: To assess elderly individuals' demand for emergency department (ED) care, in terms of the characteristics, processes, outcomes, costs by referral pattern. DATA SOURCE: All ED visits involving patients aged 65 and older, extracted from the 2010 dataset of an Local Health Agency, in North-Eastern Italy (no. = 18 648). STUDY DESIGN: Retrospective cohort study. PRINCIPAL FINDINGS: Patients were referred by primary care professionals (PCPs) in 43.1% of cases, 1.4% came from nursing homes (NH), and 55.5% were self-referred (SR). The SR group had a higher adjusted odds ratio (aOR) for non-urgent conditions (1.98 CI 1.85-2.12), but a lower aOR for conditions amenable to ambulatory care (0.53 CI 0.48-0.59), and a lower consumption of resources. The SR group tend to occur more frequently out of hours, and to coincide with a shorter stay at the ED, lower observation unit activation rates, lower hospitalization rates and a lower consumption of services than other two groups. The average costs for all procedures were lower for the SR patients (mean = 106.04 € ± SD 84.90 €) than for those referred by PCPs (mean = 138.14 € ± SD 101.17 €) or NH (mean = 143.48 € ± SD 95.28 €). CONCLUSION: Elderly patients coming in ED have different characteristics, outcomes and recourses consume by referral pattern.